5x + (3x)^2 for x=-2 5* 3+ (3*2) ^2 15 + (6) ^2 15+36 51
Follow Math Help Forum on Facebook and Google+
Originally Posted by breanna2471 5x + (3x)^2 for x=-2 5* 3+ (3*2) ^2 15 + (6) ^2 15+36 51 no it isn't, x = -2, you plugged in x = 3 for 5x
Originally Posted by breanna2471 5x + (3x)^2 for x=-2 5* 3+ (3*2) ^2 15 + (6) ^2 15+36 51 ok, we have 5x + (3x)^2 and we want to evaluate it when x = -2. this simply means that we replace x with -2 wherever we see it in the formula. 5x + (3x)^2 = 5(-2) + (3*-2)^2 .................= -10 + (-6)^2 .................= -10 + 36 .................= 26
you have been very helpful i really appreciate your help
View Tag Cloud